2009
DOI: 10.1029/2009gl038527
|View full text |Cite
|
Sign up to set email alerts
|

Rock seismic anisotropy of the low‐velocity zone beneath the volcanic front in the mantle wedge

Abstract: Peridotite xenoliths derived from the low velocity zone beneath the Avacha frontal volcano, Kamchatka, preserve a‐axis slip fabrics, comparable with those in xenoliths from the back‐arc region of the NE Japan. Although low‐velocity zones are commonly attributed to zones of partially melted mantle, migration of the melt does not erase the existing olivine fabrics and related seismic anisotropies. These anisotropies may counteract the anisotropies associated with c‐axis slip fabrics, if they exist, along the sla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
3
9
0
1
Order By: Relevance
“…This anisotropy pattern is typical of peridotites which olivine CPO has an orthorhombic or axial [100] symmetry [ Tommasi et al , 2004; Vauchez et al , 2005]. It is also in good agreement with the seismic properties calculated for another Avacha volcano xenolith collection by Michibayashi et al [2009]. Moreover, Vp/Vs 1 and Vp/Vs 2 ratios are minimum for propagation directions at high angle (>30°) to the lineation and the foliation, respectively.…”
Section: Seismic Propertiessupporting
confidence: 81%
“…This anisotropy pattern is typical of peridotites which olivine CPO has an orthorhombic or axial [100] symmetry [ Tommasi et al , 2004; Vauchez et al , 2005]. It is also in good agreement with the seismic properties calculated for another Avacha volcano xenolith collection by Michibayashi et al [2009]. Moreover, Vp/Vs 1 and Vp/Vs 2 ratios are minimum for propagation directions at high angle (>30°) to the lineation and the foliation, respectively.…”
Section: Seismic Propertiessupporting
confidence: 81%
“…The anisotropy in the mantle wedge results from the LPO of olivine caused by the subduction‐driven back‐arc spreading and mantle convection [ Nicolas and Christensen , 1987; Karato et al , 2008; Wiens et al , 2008]. Based on the stress field and thermal structure of the upper mantle beneath NE Japan, several recent studies suggested that, while deformation throughout most of the mantle wedge is controlled by diffusion creep, the anisotropic zone of dislocation creep is limited to a thin layer with relatively high stress and low temperature located right above the subducting slab and another thin layer right beneath the island arc crust [ Katayama , 2009; Michibayashi et al , 2006, 2009]. Recent P wave anisotropic tomography shows that the anisotropy in the central portion of the mantle wedge is weaker than that in the uppermost mantle and atop the subducting slab [ Wang and Zhao , 2008, 2010; Eberhart‐Phillips and Reyners , 2009; Huang et al , 2011].…”
Section: Anisotropy In the Mantle Wedge And The Slabmentioning
confidence: 99%
“…C-type LPO has been detected in rocks from the deep upper mantle such as those from Alpe Arami in Switzerland (Frese et al 2003), Ugelvik in Norway , Sulu ultra-high pressure terrane in Eastern China (Xu et al 2006;Wang et al 2013), and the North Qaidam ultrahigh pressure belt in northwestern China (Jung et al 2013). In addition, numerous studies have reported the deformation microstructures of olivine derived from subduction zones (Mehl et al 2003;Mizukami et al 2004;Michibayashi et al 2009) and collision zones (Skemer et al 2006;Tommasi et al 2006;Jung 2009;Palasse et al 2012;Michibayashi & Oohara 2013;Jung et al 2014). However, studies of the deformation microstructures of olivine related to mantle metasomatism in continental rift zones have been very limited.…”
Section: Introductionmentioning
confidence: 99%